CULTIVATING CHILDREN'S CHARACTER IN THE FAMILY OF 'AISYIYAH WATUKEBO JEMBER BRANCH - Muhammad Abdul Basit (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2022)
The Strengthening Character Education Movement is very important to be a concern and commitment for every parent who has children, especially mothers as madrasatul ula. As an effort to instill good character in children, 'Aisyiyah has long initiated the concept of a sakinah family. In addition to regular weekly recitations, the concept of a sakinah family in 'Aisyiyah Watukebo Jember Branch is studied through the student guardian parenting program in assisted schools.This study aims to examine (1) mothers' understanding of the characters of religion, nationalism, independence, mutual cooperation and integrity; (2) mothers' patterns in instilling these characters in their families; and (3) factors that become obstacles and supporters of mothers in instilling these characters. This research uses a mini-ethnography case study design that focuses on a particular phenomenon by conducting short and intensive field research. The data analysis used is Wolcott's model which includes description, analysis, and interpretation.This research was conducted in the neighborhood of 'Aisyiyah Watukebo Jember Branch. There were three mothers who became research subjects, namely Mrs. Suprihatin, Mrs. Arum and Mrs. Efi. The results showed that (1) mothers have several differences in understanding the religious, nationalist, independent, gotong-royong and integrity character of children. In the pattern of cultivating children's character, the three of them have completed the principles of a sakinah family with various educational patterns; (2) Mrs. Suprihatin and Mrs. Arum are the same.